The credibility of the digital media: Teacher perceptions and practice - Widia Murni Wijaya; Slamet Lestari; Tina Rahmawati; Maria Margaretha Wahyuningrum Handayani; Thuok David (Jurnal Akuntabilitas Manajemen Pendidikan, 2022)
The current digital literacy skill that teachers have to master is the ability to determine the credibility of the digital media for education used to support distance learning. The teachers were asked to sort several digital media and differentiate which digital media provided many benefits and best facilitate learning. This research was comparative quantitative research. The participants were 108 teachers directed to assess the credibility of digital media to compare between high and low credibility. The purpose of this study was to understand how teachers determine the credibility of the digital media whether they decided based on star reviews or the number of the features provided by the digital media that were used to facilitate learning. The results shown that when using the digital media with high star reviews, the digital media with more features gained more credibility, on the other hand, the digital media with fewer features were not able to compensate for the low star reviews. The ultimate goal proposed is to change the attitude and behavior of the teacher. When the teacher knew the information and chose the digital media to use, the teacher finds a change in their attitude. In general, digital media use in learning tends to be seen from the star reviews given by digital media users, which can trigger credibility assessment.